A new distinctively banded species of Pseudolithoxus (Siluriformes: Loricariidae) from the upper Orinoco River - Lujan, Nathan K.; Birindelli, Jose L. O. (Zootaxa, 2011)
Pseudolithoxus kelsorum is described as a new species based on type material from the upper Orinoco in Amazonas State, Venezuela. Pseudolithoxus kelsorum is diagnosed from all other Pseudolithoxus by having dark brown to black base color with eight to 11 (usually nine) light yellow vertical or oblique transversal bands between orbits and caudal fin, bands wide and rarely but sometimes incomplete or contorted as swirls (vs. dark brown to black base color with 18 or more thin, light yellow, frequently contorted transversal bands between orbits and caudal fin in P. tigris; black base color with small white spots in P. anthrax and P. nicoi; and light brown base color with dark brown to black spots in P. dumus). Distributions of P. kelsorum and other Ancistrini taxa support the presence of a zoogeographic filter limiting fish distributions across a reach of the Orinoco River between the Ventuari-Orinoco confluence and the Maipures rapids.